BAHASA, KEKUASAAN, DAN RESISTANSINYA: STUDI TENTANG NAMA-NAMA BADAN USAHA DI DAERAH ISTIMEWA YOGYAKARTA - I Dewa Putu Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
This paper aims to describe the domination of foreign languages on the use of Indonesian and local languages, and the resistance of the dominated languages in the naming of public enterprises in Yogyakarta. All data presented in this paper are obtained through observation to the public enterprise names found in Yogyakarta and classified based on their origin and the ways of creating resistence. The investigation yields that besides the most prominent English, there are several other foreign languages which influence theenterprise naming practices. Those are Arabic, Italy, France, Chinese, and Japanese. In some cases, the dominated Indonesian and Javanese show resistance by creating names which are orthographically, lexically, and grammatically resamble or similar to the expressions of the dominated languages. The domination should be seriously aware of by all Indonesian communities in order to succesfully maintain the sustainable existence of Indonesian and the local languages.